Perception of Shared Spaces in Collective Housing and the Applicability of Cohousing Model Principles: A Case Study of Belgrade - Milošević Pantović, Aleksandra M. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
The paper explores the application of cohousing principles in contemporary collective housing, focusing on the role of design in shaping social interactions. Based on a survey of architecture students in Belgrade, it examines perceptions of shared spaces and acceptable social engagement. Results show a preference for flexible, semi-open spaces for spontaneous encounters, while spaces perceived as highly obligatory tend to provoke resistance. Despite support for collective values, willingness to redefine privacy is limited. Findings suggest shared spaces in Belgrade are treated as supplementary rather than integral, and cohousing principles can be applied selectively through graduated interaction without imposing communality.